Multilayer negative plate, preparation method and application thereof
By adopting a multi-layer negative electrode sheet structure in the sodium ion battery, the high capacity of the first active material layer and the high magnification characteristics of the second active material layer are solved, and the polarization problem and capacity of the sodium ion battery during high-speed charging are solved. Pushing into the problem, achieving efficient charging and stable performance.
Patent Information
- Application Number
- CN202411597613.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
It is difficult to find a balance between high capacity and high magnification, resulting in polarization problems and capacity impulse problems during high magnification fast charging, affecting the battery's charging and discharging efficiency and life.
A multi-layer negative electrode sheet structure is adopted, wherein the first active material layer has a high capacity, can store more sodium ions, and continue to rush into the remaining capacity after the constant current stage is over; the second active material layer has a high magnification and can respond quickly Charging with high current to reduce polarization. By reasonably matching these two layers of materials, the polarization problem and capacity impulse problem of sodium ion batteries during high-speed charging are solved.
The charging efficiency of sodium ion batteries is improved, the risk of sodium extraction is avoided, and a multi-layer negative electrode sheet with high capacity and high magnification is obtained, which improves the overall performance of the battery.
Smart Images

Figure CN119480891A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery negative electrode, in particular to a multilayer negative electrode sheet, a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have broad application prospects in electric vehicles, energy storage, renewable energy storage, portable electronic devices and many other fields. In order to better meet the performance requirements in different application scenarios, the existing technology is eager to obtain high-capacity and high-rate sodium-ion batteries. As for sodium-ion batteries, in order to improve the capacity of the negative electrode material, the use of multi-pore means is an effective way, because the porous structure can increase the specific surface area of the material, provide more sodium storage sites, thereby promoting the occurrence of electrode reactions and increasing the capacity. However, multi-pores will increase the BET of the negative electrode material. Excessive BET will cause too much solid electrolyte membrane (SEI membrane) to be formed during the first charge and discharge process, which will not only consume too much sodium, but also reduce the first coulombic efficiency of the material. Therefore, in order to overcome the above defects, the negative electrode material needs to be coated after multi-pores. Coating can not only reduce the specific surface area of the negative electrode material, reduce the amount of SEI membrane formed, and reduce irreversible capacity loss, but also improve cycle stability and structural integrity, and optimize electrochemical performance. However, coating will lead to a weakening of the rate performance of the negative electrode, which will have an adverse effect on the charging and discharging efficiency and speed, discharge performance, battery life and stability of the sodium-ion battery. That is, high-capacity materials are difficult to fast charge, while the capacity of materials that support fast charging is small, and high capacity and high rate cannot be achieved at the same time.
[0003] How to find a balance between high capacity and high rate to obtain a sodium-ion battery with both high capacity and high rate is a higher requirement that the market has placed on existing sodium-ion batteries. For this reason, this application is filed. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a multilayer negative electrode sheet, a preparation method and application thereof.
[0005] Firstly, the present invention provides a multi-layer negative electrode sheet.
[0006] A multilayer negative electrode sheet, comprising a current collector and active material layers formed on both sides of the current collector, wherein the active material layers comprise a first active material layer located on the surface of the current collector and a second active material layer located on the surface of the first active material layer;
[0007] The specific surface area, surface density and compacted density of the first active material layer are BET1, ρ1 and CD1 respectively. The first active material layer satisfies: 3.00m 2 / g≤BET1≤6.00m 2 / g, 3.00mg / cm2 ≤ρ1≤5.00mg / cm 2 , 0.80g / cm 2 ≤CD1≤1.30g / cm 2 , 3.00μm≤Dv50≤8.00μm, 0.40≤Dn10 / Dn50≤0.60;
[0008] The specific surface area, surface density and compacted density of the second active material layer are BET2, ρ2 and CD2 respectively. The second active material layer satisfies: 6.00 m 2 / g≤BET2≤13.00m 2 / g, 5.00mg / cm 2 ≤ρ2≤8.00mg / cm 2 , 0.80g / cm 2 ≤CD2≤1.30g / cm 2 , 2.00μm≤Dv50≤7.00μm, 0.60≤Dn10 / Dn50≤0.80;
[0009] And 0.70≤CD1 / CD2≤1.50, 0.23≤BET1 / BET2≤0.80.
[0010] During high-rate fast charging, the polarization problem caused by dynamics inside the battery causes the current acceptance capacity in the constant current charging stage to decrease, the constant current charge is relatively low, and more capacity needs to be charged in the subsequent constant voltage stage.
[0011] In the present invention, the first active material layer has a high capacity and can store more sodium ions. When the constant current stage ends, the sodium ions on the surface will transfer to the first active material layer and continue to charge into the remaining capacity, which not only avoids the problem of overcharging and sodium precipitation of the battery due to the increase in the constant voltage stage time, but also helps to reduce the constant voltage stage time and improve the charging efficiency; the second active material layer has a high rate, on the one hand, it can quickly respond to large current charging, reduce polarization, and enable the battery to charge into more capacity in the constant current stage, and on the other hand, it helps to reduce the internal resistance of the battery, improve the charge transfer efficiency, and further reduce polarization; the first active material layer and the second active material layer work together and influence each other, and finally a multilayer negative electrode sheet with both high capacity and high rate performance is obtained.
[0012] Preferably, 0.80≤CD1 / CD2≤1.20, for example, it can be 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0013] Further preferably, 0.83≤CD1 / CD2≤1.00, for example, it can be 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0014] Preferably, 0.23≤BET1 / BET2≤0.60, for example, it can be 0.23, 0.28, 0.33, 0.38, 0.43, 0.48, 0.53, 0.58, or 0.60, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0015] Further preferably, 0.3≤BET1 / BET2≤0.45, for example, it can be 0.30, 0.32, 0.34, 0.36, 0.38, 0.40, 0.42, 0.44, 0.45, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0016] Preferably, ρ1 and ρ2 satisfy: 8.00 mg / cm 2 ≤ρ1+ρ2≤11.00mg / cm 2 , for example, it can be 8.00 mg / cm 2 、8.20mg / cm 2 、8.50mg / cm 2 、8.80mg / cm 2 、9.00mg / cm 2 , 9.20mg / cm 2 , 9.50mg / cm 2 , 9.80mg / cm 2 、10.00mg / cm 2 、10.20mg / cm 2 、10.50mg / cm 2 、10.80mg / cm 2 、11.00mg / cm 2 , but is not limited to the listed values, other values not listed within the numerical range are also applicable.
[0017] The present invention has found through several innovative experiments that if ρ1+ρ2>11.00, the obtained negative electrode sheet has poor effect on improving the capacity and charge-discharge performance of the sodium ion battery. The reason may be that the excessive surface density of the negative electrode makes it difficult for sodium ions to intercalate, affecting the battery capacity and charge-discharge performance, and there may be areas that are not embedded by sodium ions, that is, dead areas, which not only waste negative electrode materials but also affect the overall performance of the battery. In addition, if ρ1+ρ2>11.00, the processing of the obtained negative electrode sheet also becomes difficult, which can easily lead to the electrode sheet being crushed to death during the rolling process, and it is also easy to increase the brittleness of the negative electrode sheet, which is easy to break during the processing, affecting the yield rate and battery assembly.
[0018] Preferably, the active material in the first active material layer includes hard carbon and hard carbon doped with metal or non-metal elements, the active material in the second active material layer includes hard carbon, expanded graphite and transition metal oxides, and the current collector is aluminum foil.
[0019] Secondly, the present invention provides a method for preparing a multi-layer negative electrode sheet.
[0020] A method for preparing a multilayer negative electrode sheet, specifically comprising the following steps: firstly coating a first active material slurry on two surfaces of a current collector, drying it, rolling it and achieving a specified compaction density to obtain a first active material layer, then coating a second active material slurry on the surface of the first active material layer, drying it, rolling it again and achieving a specified compaction density to obtain a second active material layer, and finally cutting it to obtain a multilayer negative electrode sheet.
[0021] Preferably, the first active material slurry and the second active material slurry both use water as a solvent and sodium carboxymethyl cellulose and / or styrene-butadiene rubber as a binder.
[0022] Thirdly, the present invention also proposes a sodium ion battery, which comprises the above-mentioned multi-layer negative electrode sheet.
[0023] In addition, the sodium ion battery also includes a positive electrode sheet, an electrolyte and a separator, which are conventional choices in the art.
[0024] Compared with the prior art, the present invention arranges a first active material layer and a second active material layer with specific specific surface area, surface density, compacted density and particle size on both sides of the current collector, and effectively solves the polarization problem and capacity rush problem of sodium ion batteries during high-rate fast charging by reasonably matching high-capacity material layers and high-rate materials. It not only improves the charging efficiency of sodium ion batteries, but also avoids the risk of sodium precipitation. Finally, a multi-layer negative electrode sheet with both high capacity and high rate is obtained, which provides strong support for the high-performance fast charging of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is a schematic structural diagram of a multi-layer negative electrode sheet proposed by the present invention.
[0027] Among them: 1. current collector; 2. first active material layer; 3. second active material layer. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0029] The raw materials used in the following examples and comparative examples were all commercially available. The operations not described in detail in the following examples and comparative examples are all conventional techniques in the art.
[0030] Example 1
[0031] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%: 1.5%: 1.5%: 2% by mass, and 2% by mass of NMP was added, and then 2% by mass of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 4.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0032] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93%:3%:2%:2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 10.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0033] (3) The first active material slurry was coated with 4.00 mg / cm 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 0.90g / cm2 , and then 5.00mg / cm per side 2 The surface density of the second active material slurry is continued to be evenly coated on the surface, dried and rolled to a compacted density of 0.96g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0034] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0035] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0036] Example 2
[0037] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were added in the order of 95% by mass: 1.5% by mass: 1.5% by mass: 2% by mass, and then 2% by mass of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 4.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0038] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93%:3%:2%:2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 10.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0039] (3) The first active material slurry was coated at a density of 3.00 mg / cm per side. 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 0.90g / cm 2 , and then follow the single side 6.00mg / cm 2 The surface density of the second active material slurry is continued to be evenly coated on the surface, dried and rolled to a compacted density of 0.93g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0040] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0041] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0042] Example 3
[0043] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%: 1.5%: 1.5%: 2% by mass, and 2% by mass of NMP was added, and then 2% by mass of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 4.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0044] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93%:3%:2%:2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 10.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0045] (3) The first active material slurry was coated with 4.00 mg / cm 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 0.89g / cm 2 , and then 5.00mg / cm per side 2 The surface density of the second active material slurry is further uniformly coated on the surface, dried and rolled to a compacted density of 1.01 g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0046] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0047] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0048] Example 4
[0049] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%: 1.5%: 1.5%: 2% by mass, and 2% by mass of NMP was added, and then 2% by mass of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 4.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0050] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in a mass percentage of 93%:3%:2%:2%, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 10.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0051] (3) The first active material slurry was coated with 4.00 mg / cm 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 0.89g / cm 2 , and then 5.00mg / cm per side 2 The surface density of the second active material slurry is continued to be evenly coated on the surface, dried and rolled to a compacted density of 0.95g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0052] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0053] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0054] Example 5
[0055] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%:1.5%:1.5%:2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 6.40 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0056] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93% by mass: 3% by mass: 2% by mass: 2% by mass, and 2% by mass of NMP was added, and then 2% by mass of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 8.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0057] (3) The first active material slurry was coated at a density of 3.00 mg / cm per side. 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 0.91g / cm 2 , and then 5.00mg / cm per side 2 The surface density of the second active material slurry is continued to be evenly coated on the surface, dried and rolled to a compacted density of 1.30 g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0058] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0059] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0060] Example 6
[0061] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%: 1.5%: 1.5%: 2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 4.20 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0062] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93% by mass: 3% by mass: 2% by mass: 2% by mass, and 2% by mass of NMP was added, and then 2% by mass of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 6.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0063] (3) The first active material slurry was coated with 4.00 mg / cm 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 0.80g / cm 2 , and then follow the single side 6.00mg / cm 2 The surface density of the second active material slurry is continued to be evenly coated on the surface, dried and rolled to a compacted density of 1.00 g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0064] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0065] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0066] Example 7
[0067] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%: 1.5%: 1.5%: 2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 6.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0068] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93%:3%:2%:2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 10.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0069] (3) The first active material slurry was coated at a density of 3.00 mg / cm per side. 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 1.00g / cm 2 , and then 7.00mg / cm per side 2 The surface density of the second active material slurry is continued to be evenly coated on the surface, dried and rolled to a compacted density of 1.20 g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0070] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0071] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0072] Example 8
[0073] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%: 1.5%: 1.5%: 2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 3.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0074] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93%:3%:2%:2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 6.70 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0075] (3) The first active material slurry was coated at a density of 3.00 mg / cm per side. 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 1.10g / cm 2 , and then 8.00mg / cm per side 2 The surface density of the second active material slurry is continued to be evenly coated on the surface, dried and rolled to a compacted density of 1.20 g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0076] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0077] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0078] Example 9
[0079] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%: 1.5%: 1.5%: 2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 3.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0080] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93%:3%:2%:2% by mass, and 2% of NMP was added, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 7.50 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0081] (3) The first active material slurry was coated with 4.00 mg / cm 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 0.80g / cm 2 , and then 5.00mg / cm per side 2 The surface density of the second active material slurry is further uniformly coated on the surface, dried and rolled to a compacted density of 0.80 g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0082] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0083] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0084] Example 10
[0085] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%:1.5%:1.5%:2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 3.90m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0086] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93% by mass: 3% by mass: 2% by mass: 2% by mass, and 2% by mass of NMP was added, and then 2% by mass of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 13.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0087] (3) The first active material slurry was coated at a density of 5.00 mg / cm per side. 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 1.30g / cm 2 , and then 5.00mg / cm per side 2 The surface density of the second active material slurry is continued to be evenly coated on the surface, dried and rolled to a compacted density of 1.10 g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0088] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0089] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0090] Embodiment 11
[0091] (1) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 95%: 1.5%: 1.5%: 2% by mass, and 2% of NMP was added to the total mass, and then 2% of CMC aqueous solution was added and stirred evenly to obtain a first active material slurry with a solid content of 50%. The BET of the hard carbon was 3.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.50;
[0092] (2) Hard carbon, conductive agent SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were mixed in the order of 93% by mass: 3% by mass: 2% by mass: 2% by mass, and 2% by mass of NMP was added, and then 2% by mass of CMC aqueous solution was added and stirred evenly to obtain a second active material slurry with a solid content of 65%. The BET of the hard carbon was 13.00 m 2 / g, Dv50 is 5.00μm, Dn10 / Dn50 is 0.70;
[0093] (3) The first active material slurry was coated with 4.00 mg / cm 2 The surface density is evenly coated on the surface of the aluminum foil, dried and rolled to a compacted density of 1.20g / cm 2 , and then 5.00mg / cm per side 2 The surface density of the second active material slurry is further uniformly coated on the surface, dried and rolled to a compacted density of 0.80 g / cm 2 , after cutting, the negative electrode sheet is obtained;
[0094] (4) NaCoO2, PVDF, conductive agent CNTs, and oxalic acid were mixed in the order of 96%:1.5%:2.1%:0.4% by mass, and added to NMP and stirred evenly to obtain a positive electrode active material slurry, which was then heated to 17.6 mg / cm 2 The surface density of the aluminum foil is evenly coated on the surface of the aluminum foil, and after drying, the positive electrode sheet is obtained by rolling and cutting.
[0095] (5) After the tabs of the negative electrode sheet and the positive electrode sheet are welded, they are wound with the separator to form a roll core, which is first baked to remove moisture and then packaged with an aluminum-plastic film. After that, an electrolyte is injected to seal and form a sodium ion battery.
[0096] Comparative Example 1
[0097] Compared with Example 1, the compaction density of the second active material layer was adjusted to 0.60 g / cm 2 , and the rest are consistent with Example 1.
[0098] Comparative Example 2
[0099] Compared with Example 1, the compaction density of the first active material layer was adjusted to 0.60 g / cm 2 , and the rest are consistent with Example 1.
[0100] Comparative Example 3
[0101] Compared with Example 1, the BET1 of the first active material layer was adjusted to 2.80 m 2 / g, and the BET2 of the second active material layer was adjusted to 13.7m 2 / g, and the rest are consistent with Example 1.
[0102] Comparative Example 4
[0103] Compared with Example 1, the BET1 of the first active material layer was adjusted to 5.60 m 2 / g, and the BET2 of the second active material layer was adjusted to 4.70m 2 / g, and the rest are consistent with Example 1.
[0104] Comparative Example 5
[0105] Compared with Example 1, Dn10 / Dn50 of the first active material layer is adjusted to 0.84, and Dn10 / Dn50 of the second active material layer is adjusted to 0.73, and the rest are consistent with Example 1.
[0106] Comparative Example 6
[0107] Compared with Example 1, Dn10 / Dn50 of the first active material layer is adjusted to 0.47, and Dn10 / Dn50 of the second active material layer is adjusted to 0.49, and the rest are consistent with Example 1.
[0108] Comparative Example 7
[0109] Compared with Example 1, the first active material slurry is 5.00 mg / cm 2 The surface density of the second active material slurry is uniformly coated on the surface of the aluminum foil at 7.00 mg / cm 2 The surface density is coated, and the rest are consistent with Example 1.
[0110] Comparative Example 8
[0111] Compared with Example 1, the compaction density of the first active material layer was adjusted to 1.50 g / cm 2 , and the rest are consistent with Example 1.
[0112] Comparative Example 9
[0113] Compared with Example 1, the compaction density of the second active material layer was adjusted to 1.50 g / cm 2, and the rest are consistent with Example 1.
[0114] The main technical parameters of each embodiment and comparative example are shown in Table 1.
[0115] Table 1 Main technical parameters of each embodiment and comparative example
[0116]
[0117]
[0118] The above embodiments and comparative examples were tested for various properties using the following methods, and the test results are shown in Table 2:
[0119] (1) Negative electrode peeling force test
[0120] The prepared negative electrode sheet was tested for peeling force using a universal testing machine. The test conditions for the peeling force of the universal testing machine were set as follows: select "T-type peeling test mode", set the initial distance between the two chucks of the tester to 30mm, the tensile speed to 200mm / min, and the chuck displacement to 50-80mm. During the test, pay attention to the verticality of the upper and lower clamps of the spline and the spline. The spline is not allowed to tilt. The test can be stopped when the output peeling value is stable. The specific operation is: stick a layer of 3M tape on the rolled negative electrode sheet to prepare 3 splines with a width of 20mm and a length of 200mm for testing. With the assistance of 3M tape, peel off the slurry layer 1 and the film layer 2 of the spline by 2-3cm. Take the average value of 3 tests. The greater the peeling strength, the stronger the adhesion of the electrode sheet.
[0121] (2) Battery performance test
[0122] The prepared sodium ion battery was tested in the voltage range of 2.0-3.95V, and its electrochemical performance was investigated at 1C / 1C, 2C / 2C, 3C / 3C 500 times capacity retention rate and 5C constant current charge ratio.
[0123] Table 2 Performance test results of various embodiments and comparative examples
[0124]
[0125]
[0126] like Figure 1 , as shown in Table 1 and Table 2:
[0127] It can be seen from Examples 1 to 11 that under the conditions specified in the present invention, the peeling force of the obtained negative electrode sheets is 4.2 N / m or above. After being assembled into sodium ion batteries, the capacity retention rates of 1C / 1C and 500 cycles are 98.2% or above, the capacity retention rates of 2C / 2C and 500 cycles are 96.5% or above, the capacity retention rates of 3C / 3C and 500 cycles are 95.1% or above, the 5C constant current charge ratio is 85.2% or above, the overall cycle performance and rate performance are good, and during the entire charge and discharge process, the two active material layers do not fall off or delaminate, and the overall structure of the negative electrode sheet is stable and complete.
[0128] By comparing Comparative Example 1 with Example 1, it can be seen that if the compaction density of the second active material layer is too low, the sodium ion diffusion path will become longer, which will not only affect the downward deposition of sodium ions in the battery, but also affect the infiltration of the electrolyte, resulting in degradation of high-rate cycle performance and a low 5C constant current injection ratio. In addition, it also leads to a decrease in the peeling force of the negative electrode sheet and a deterioration in the adhesion of the active material layer. By comparing Comparative Example 2 with Example 1, it can be seen that if the compaction density of the first active material layer is too low, the bonding between the first active material layer and the current collector is not tight enough, resulting in a decrease in the peeling force of the negative electrode sheet, and the active material layer may fall off or delaminate during the charge and discharge process. In theory, the compaction density is too small, which means that less active material can be stored in the same volume, and therefore the capacity of the battery cell will also decrease. Moreover, it also indirectly affects the rate performance, resulting in a deterioration trend in the rate performance.
[0129] By comparing Comparative Example 3 with Example 1, it can be seen that: if the BET of the first active material layer is small, the deposition of sodium ions is slow, while the BET of the second active material layer is large, the battery rate performance is greatly improved, and the second active material layer has more constant current charge ratios, but the battery as a whole is shallow charge and discharge, so the cycle performance is poor. By comparing Comparative Example 4 with Example 1, it can be seen that: if the BET of the second active material layer is small, the polarization problem is more serious when charging at a high rate, so the rate cycle performance deteriorates, and the 5C constant current charge ratio is low.
[0130] By comparing Comparative Example 5 with Example 1, it can be seen that if there are too many fine powders in the first active material layer and the second active material layer, the adhesion on the current collector will be poor, and the peeling force of the negative electrode sheet will be significantly reduced, not only the processability is poor, but also it is easy to fall off during cycling. By comparing Comparative Example 6 with Example 1, it can be seen that if there are too few fine powders in the first active material layer and the second active material layer, although there is good adhesion on the current collector, it will lead to a decrease in the constant current charge ratio during high rate charging.
[0131] By comparing Comparative Example 7 with Example 1, it can be seen that under the premise that other conditions are completely consistent, if the surface density of the first active material layer and the second active material layer increases (the sum of the surface density is greater than 11), the cycle performance and rate performance of the battery are significantly deteriorated. The reason for this is that the excessive surface density makes it difficult for sodium ions to intercalate, and dead areas that are not embedded by sodium ions are likely to appear, thus causing the overall performance of the battery to deteriorate.
[0132] By comparing Comparative Examples 8 and 9 with Example 1, it can be seen that: under the premise that other conditions are completely consistent, if the compaction density of the first active material layer or the compaction density of the second active material layer is increased, the corresponding active material hard carbon will be over-pressurized, and the hard carbon over-pressurization will cause peeling and poor wettability to the electrolyte, which will lead to significant degradation of the cycle performance and rate performance. In addition, by comparing Comparative Examples 8 and 9, it can be seen that the second active material layer of Comparative Example 8 can still provide objective capacity to slow down the deterioration of the cycle performance of the battery cell, while the over-pressurization of the second active material layer of Comparative Example 9 will affect the compactness of the first active material layer, significantly reducing the wettability of the electrolyte, thereby causing more obvious degradation of the cycle performance and rate performance.
[0133] In summary: the present invention arranges a first active material layer and a second active material layer with specific specific surface area, surface density, compacted density and particle size on both sides of the current collector, and effectively solves the polarization problem and capacity rush problem of sodium ion batteries during high-rate fast charging by reasonably matching high-capacity material layers and high-rate materials. It not only improves the charging efficiency of sodium ion batteries, but also avoids the risk of sodium precipitation. Finally, a multilayer negative electrode sheet with both high capacity and high rate is obtained, and its use in sodium ion batteries helps to improve the overall performance of the battery.
[0134] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A multi-layer negative electrode sheet, characterized in that: It comprises a current collector (1) and active material layers formed on both sides of the current collector (1), wherein the active material layers comprise a first active material layer (2) located on the surface of the current collector (1) and a second active material layer (3) located on the surface of the first active material layer (2); The specific surface area, surface density and compacted density of the first active material layer (2) are BE T1, ρ1 and CD1 respectively. The first active material layer satisfies: 3.00 m 2 / g≤BET1≤6.00m 2 / g, 3.00mg / cm 2 ≤ρ1≤5.00mg / cm 2 , 0.80g / cm 2 ≤CD1≤1.30g / cm 2 , 3.00μm≤Dv50≤8.00μm, 0.40≤Dn10 / Dn50≤0.60; The specific surface area, surface density and compacted density of the second active material layer (3) are BE T2, ρ2 and CD2 respectively. The second active material layer satisfies: 6.00 m 2 / g≤BET2≤13.00m 2 / g, 5.00mg / cm 2 ≤ρ2≤8.00mg / cm 2 , 0.80g / cm 2 ≤CD2≤1.30g / cm 2 , 2.00μm≤Dv50≤7.00μm, 0.60≤Dn10 / Dn50≤0.80; And 0.70≤CD1 / CD2≤1.50, 0.23≤BET1 / BET2≤0.
80.
2. The multilayer negative electrode sheet according to claim 1, characterized in that: 0.80≤CD1 / CD2≤1.
20.
3. The multi-layer negative electrode sheet according to claim 2, characterized in that: 0.83≤CD1 / CD2≤1.
00.
4. The multi-layer negative electrode sheet according to claim 1, characterized in that: 0.23≤BET1 / BET2≤0.
60.
5. The multi-layer negative electrode sheet according to claim 4, characterized in that: 0.30≤BET1 / BET2≤0.
45.
6. The multi-layer negative electrode sheet according to claim 1, characterized in that: ρ1, ρ2 meet: 8.00mg / cm 2 ≤ρ1+ρ2≤11.00mg / cm 2 .
7. The multilayer negative electrode sheet according to any one of claims 1 to 6, characterized in that: The active material in the first active material layer (2) includes hard carbon and hard carbon doped with metal or non-metal elements, the active material in the second active material layer (3) includes hard carbon, expanded graphite and transition metal oxides, and the current collector (1) is aluminum foil.
8. A method for preparing a multilayer negative electrode sheet according to any one of claims 1 to 7, characterized in that: The specific operation is as follows: firstly, a first active material slurry is coated on two surfaces of a current collector (1), and then rolled after drying to obtain a first active material layer (2) at a specified compaction density; then, a second active material slurry is coated on the surface of the first active material layer (2), and then rolled again after drying to obtain a second active material layer (3); and finally, the multilayer negative electrode sheet is cut to obtain the multilayer negative electrode sheet.
9. The method for preparing a multi-layer negative electrode sheet according to claim 8, characterized in that: The first active material slurry and the second active material slurry both use water as a solvent and sodium carboxymethyl cellulose and / or styrene-butadiene rubber as a binder.
10. A sodium ion battery, characterized in that: It comprises a multilayer negative electrode sheet as described in any one of claims 1 to 7 or a multilayer negative electrode sheet prepared according to the preparation method as described in claim 8 or 9.